2007
DOI: 10.3748/wjg.v13.i32.4295
|View full text |Cite
|
Sign up to set email alerts
|

Female hepatology: Favorable role of estrogen in chronic liver disease with hepatitis B virus infection

Abstract: Chronic hepatitis B virus (HBV) infection is the most common cause of hepatic fibrosis and hepatocellular carcinoma (HCC), mainly as a result of chronic necroinflammatory liver disease. A characteristic feature of chronic hepatitis B infection, alcoholic liver disease and nonalcoholic fatty liver disease (NAFLD) is hepatic steatosis. Hepatic steatosis leads to an increase in lipid peroxidation in hepatocytes, which, in turn, activates hepatic stellate cells (HSCs). HSCs are the primary target cells for inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
115
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 122 publications
7
115
0
Order By: Relevance
“…1 It confirms that, apart from autoimmune diseases, hepatic fibrosis is largely a male disease. 1,2 This gender susceptibility has been substantiated by other epidemiological and experimental studies. 2 Estrogens have been implicated in this protective role.…”
Section: Liver and Gender: Are There Differences In Fibrous Tissue Bementioning
confidence: 67%
See 4 more Smart Citations
“…1 It confirms that, apart from autoimmune diseases, hepatic fibrosis is largely a male disease. 1,2 This gender susceptibility has been substantiated by other epidemiological and experimental studies. 2 Estrogens have been implicated in this protective role.…”
Section: Liver and Gender: Are There Differences In Fibrous Tissue Bementioning
confidence: 67%
“…1,2 This gender susceptibility has been substantiated by other epidemiological and experimental studies. 2 Estrogens have been implicated in this protective role. Yang et al reported that before and after age 50, men had 1.8-and 1.2-fold increased risk of having greater severity of fibrosis.…”
Section: Liver and Gender: Are There Differences In Fibrous Tissue Bementioning
confidence: 67%
See 3 more Smart Citations